175k views
5 votes
When solving show how to solve for X and Y individually then together.Given −x^2−4y+6xevaluate when, x=−2 and y=3

When solving show how to solve for X and Y individually then together.Given −x^2−4y-example-1

1 Answer

5 votes

So we need to evaluate this expression:


-x^2-4y+6x

In x=-2 and y=3. So we just need to replace x and y with -2 and 3:


\begin{gathered} -x^2-4y+6x=-(-2)^2-4\cdot3+6\cdot(-2) \\ -(-2)^2-4\cdot3+6\cdot(-2)=-(-2)\cdot(-2)-12-12 \\ -(-2)\cdot(-2)-12-12=-4-12-12=-28 \end{gathered}

Then the answer is -28.

User Scootermg
by
5.0k points